Impact of Electronic Word of Mouth Social Media on the Decision to Choose Nusa Penida as a Tourist Destination with Mediated e-Trust - Howard S. Giam; Yenli Megawati (Jurnal Hospitality dan Pariwisata, 2019)
ABSTRACTBased on data published by the Badan Pusat Statistik (BPS), it shows that the popularity of Indonesian tourism is increasing and making Indonesian tourism one of the country's main income sectors. One of the tourist destinations that has been increasing lately, which can be seen from the increasing number of tourist visits, is Nusa Penida in Klungkung Regency, Bali. The lack of infrastructure does not seem to reduce the number of tourist visits to Nusa Penida. This is inseparable from the government's efforts in promoting Nusa Penida and also the widespread information about this tourist destination on social media. For this reason, this study seeks to find out the influence of social media electronic word of mouth (e-WOM) on the decision to choose a tourist destination by taking a case study in Nusa Penida, Indonesia by using the e-Trust variable as a mediating variable. Data collection in this study was conducted through a survey using a questionnaire. The number of respondents for this study was 50 respondents, of which respondents were tourists who had social media and had visited Nusa Penida. Data analysis in this study used regression analysis which was processed using SPSS by testing it first for validity, reliability and classic assumption tests.Key words: e-WOM, e-Trust, Purchase Decision, Tourist Destination, Nusa Penida, Sosial Media